Speaking of Women's Depression and the Politics of Emotion. Issue 2 (May 2019) - Brown, Catrina
Women are at least twice as likely to experience depression as men, and up to 25% of women can expect to be depressed in their lifetimes. Depression is likely to recur in up to 85% of women, yet most women who experience depression cope on their own. Feminist research has explored the discursive, and social context of depression among women and acknowledges women's agency as they simultaneously struggle and cope with depression. "Getting on with life" is often an imperative, but begs the question what are they getting on with, especially if their lives have been significant in causing unhappiness and distress. I explore how depression is shaped by the discourse of self-management, gender performance and the notion "the good woman." Dominant depression discourses individualize, decontextualize, and emphasize personal responsibilization for the causes and treatment of depression. This produces an epistemic injustice for speaking about and coping with depression. Social work practitioners must make space for acknowledging women's resourcefulness and agency in their management of sadness and distress. We must also address not only the dangers of responsibilization, but the limitations of this approach to women's well-being.